Penerapan Sifat Shiddiq Rasulullah SAW Terhadap Anak Usia Dini - Wahyu Ningsih; Julia Amanda; Siti Nurhalimah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to find out how to apply the characteristics of Sidiq Rasulullah Sallallahu alaihi wassalam with children of this age. This old age child is the age to form the character of a human being. It is this character who will become a personality when he has grown up. One of the characteristics that must be instilled in children of this age to form good character traits is honesty. The nature of honesty is a trait that must be owned by children of this age in accordance with what has been taught by the Prophet Muhammad. Therefore, it is necessary to study about the application of the characteristics of the Shiddiq Rasulullah to these children of this age. This research uses the library research method which examines the object of the study and uses several mother-books as sources of data and also various available literature. The results show that the application of the Shiddiq Prophet's characteristics can be implemented in young children of this age. This implementation will make children of this age become honest individuals in accordance with Islamic religious law. By imitating the characteristics of Shiddiq Rasulullah in terms of being honest, children of this age can behave kindly towards people and the environment around them, they will like themselves. One of the honest qualities of the Prophet Muhammad, who could be emulated by children at this early age, was the Prophet who always said what was true in his actions, such as in preaching. Therefore, from that point on, the writer hopes that the people around this young child can apply the characteristics of the Prophet Muhammad to this young child.